2016
DOI: 10.1136/archdischild-2015-308825
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in corticosteroid-naïve and corticosteroid-treated Duchenne muscular dystrophy: what dose achieves optimal 25(OH) vitamin D levels?

Abstract: The prevalence of vitamin D deficiency and insufficiency in DMD is high. A 2-month replenishment regimen of 6000 IU and maintenance regimen of 1000-1500 IU/day was associated with optimal vitamin D levels. These data have important implications for optimising vitamin D dosing in DMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Twenty-five percent of the children with DMD had serum 25(OH)D concentrations less than 50 nmol/L, a prevalence that is comparable to previous studies, which have reported rates of vitamin D insufficiency of around 35%. 13,17 In contrast to these studies, the mean vitamin D supplementation dose in our cohort was higher (approximately 1600 IU/day) compared with average supplementation doses in other studies of 1000 to 1200 IU/day. Thus, even on higher than standardly used vitamin D supplementation doses, there is a significant rate of vitamin D deficiency in boys with DMD.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Twenty-five percent of the children with DMD had serum 25(OH)D concentrations less than 50 nmol/L, a prevalence that is comparable to previous studies, which have reported rates of vitamin D insufficiency of around 35%. 13,17 In contrast to these studies, the mean vitamin D supplementation dose in our cohort was higher (approximately 1600 IU/day) compared with average supplementation doses in other studies of 1000 to 1200 IU/day. Thus, even on higher than standardly used vitamin D supplementation doses, there is a significant rate of vitamin D deficiency in boys with DMD.…”
Section: Discussioncontrasting
confidence: 90%
“…While UV exposure was not directly measured, there was no seasonal variation of serum 25(OH)D in the boys with DMD potentially due to decreased outdoor time and sun exposure, as previously seen in other cohorts. 17 A prospective trial by Bianchi et al of 33 boys with DMD supplemented with vitamin D for 2 years with 0.8 µg/kg/day (equivalent to approximately 32 IU/ kg/day) resulted in a mean 25(OH)D concentration at the end of the trial of approximately 100 nmol/L. 25 This study reported high adherence rates to supplementation of 82%.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Poor bone health is thought to result partly from a lack of proper mechanical loading on bone, as well as chronic inflammation in dystrophic muscle that can stimulate osteoclastogenesis and bone resorption and may also contribute to delayed bone fracture healing . There is also persistent vitamin D insufficiency in most DMD patients that may affect bone health. The long‐term glucocorticoid therapy used to delay the rate of muscle decline in DMD further exacerbates bone fragility, with significant reductions in bone mineral density (BMD) and higher risk of vertebral fractures that can be painful and compromise quality of life …”
Section: Introductionmentioning
confidence: 99%
“…Finally, a retroactive study over a 16-year period from 1998 till 2014 assessed the efficacy of vitamin D supplementation in DMD [261]. They found that despite recommendations for DMD patients to supplement with vitamin D there is still a high prevalence of vitamin D deficiency/insufficiency in DMD patients.…”
Section: Targeting Inflammationmentioning
confidence: 99%